2020
DOI: 10.2147/hiv.s259792
|View full text |Cite
|
Sign up to set email alerts
|

<p>HIV Prevalence and Associated Factors in Key Groups and General Population Treated at a Health Care Institution in Colombia in 2019: A Cross-Sectional Study</p>

Abstract: Background: Research conducted on the prevalence of HIV/AIDS and its associated factors among key groups in Colombia is scarce. The few available studies show heterogeneity in their results and increasing trends of infection. This study analyses the prevalence of HIV and associated factors in key groups served at a health care institution in Colombia in 2019. Methods: We performed a cross-sectional study with the sample comprised of 5771 subjects from the general population, the LGBTI community, sex workers, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…In our study, the prevalence of HIV (0.93%) among indigenous individuals was found to be higher compared to other Brazilian indigenous populations, such as those residing in the Amazon (0.13%). 8 Although the prevalence was similar to indigenous populations in Peru (0.7%) 10 and Colombia (1.02%), 23 it exceeded the prevalence reported for the general Brazilian population (0.6%). 24 The elevated prevalence of HIV within the indigenous population of Dourados/MS may be influenced by various social determinants, including their indigenous status and the subsequent impact on their lives.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our study, the prevalence of HIV (0.93%) among indigenous individuals was found to be higher compared to other Brazilian indigenous populations, such as those residing in the Amazon (0.13%). 8 Although the prevalence was similar to indigenous populations in Peru (0.7%) 10 and Colombia (1.02%), 23 it exceeded the prevalence reported for the general Brazilian population (0.6%). 24 The elevated prevalence of HIV within the indigenous population of Dourados/MS may be influenced by various social determinants, including their indigenous status and the subsequent impact on their lives.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have described deficiencies in HIV/AIDS treatment among indigenous populations in Colombia. 23 Moreover, patients with CD4+ T lymphocyte counts below 500 cells/mL had a lower likelihood of achieving viral suppression. 6 Notably, a significant decrease in the incidence of STI was observed following treatment among indigenous illicit drug users residing in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Solicitó el tratamiento en su EPS prevalencia de VIH es baja en algunos grupos clave, y en aquellos con prevalencias más altas se registra alta movilidad y dificultades de captación, probablemente relacionadas con un contexto sociocultural de estigmatización hacia las personas con mayor riesgo para el VIH 31 .…”
Section: Discussionunclassified
“…Additionally, the research available in Medellín-Colombia generally reports the prevalence of infection in different groups, but very few analyze the intersectionality of being young with other risk conditions such as socioeconomic vulnerability or belonging to key groups. 7 Unlike the evidence available in Colombia, studies in other countries have shown the importance of investigating HIV in young MSM or those with socioeconomic vulnerability. A study in five cities in the United States in the period 1994-2011 reported that the prevalence increased in the group of young MSM aged between 23 and 29 years, it was stable in those aged between 18 and 22 years, and some cities such as Baltimore presented a greater increase in cases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the research available in Medellín-Colombia generally reports the prevalence of infection in different groups, but very few analyze the intersectionality of being young with other risk conditions such as socioeconomic vulnerability or belonging to key groups. 7 …”
Section: Introductionmentioning
confidence: 99%